F. BANDARIN, R. VAN OERS (eds.) - Reconnecting the City. The Historic Urban Landscape Approach and the Future of Urban - Ezquerra Alcázar, Isabel (ZARCH, 2018)
Francesco Bandarin y Ron Van Oers (eds.) Reconnecting the City. The Historic Urban Landscape Approach and the Future of Urban Heritage Oxford, John Wiley & Sons, 2014, 344 pp. Idioma: inglés. ISBN: 978-1-118-38398-8